2006
DOI: 10.1007/s00441-006-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure of peripheral synapses: autonomic ganglia

Abstract: Final motor neurons in sympathetic and parasympathetic ganglia receive synaptic inputs from preganglionic neurons. Quantitative ultrastructural analyses have shown that the spatial distribution of these synapses is mostly sparse and random. Typically, only about 1%-2% of the neuronal surface is covered with synapses, with the rest of the neuronal surface being closely enclosed by Schwann cell processes. The number of synaptic inputs is correlated with the dendritic complexity of the target neuron, and the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 103 publications
(148 reference statements)
2
29
0
Order By: Relevance
“…Although it was considered that frog intracardiac neurons have no dendrites [4], previous study has shown abundance of dendrite-like processes on the hillock and the proximal axon of frog intracardiac neurons [1]. Th ese processes do not terminate with synaptic boutons [1].…”
Section: Discussionmentioning
confidence: 97%
“…Although it was considered that frog intracardiac neurons have no dendrites [4], previous study has shown abundance of dendrite-like processes on the hillock and the proximal axon of frog intracardiac neurons [1]. Th ese processes do not terminate with synaptic boutons [1].…”
Section: Discussionmentioning
confidence: 97%
“…[42] Most neurons are noradrenergic and supply the stomach, spleen, pancreas, small intestine and mesen-teric blood vessels. [43] In the current study, we identified small, medium and large sized neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The first type provides innervation to the parenchyma of the target organs, while the second mainly innervates blood vessels. The third type innervates the sweat glands (Gibbins and Morris, 2006;Smolen, 1988).…”
Section: P0180mentioning
confidence: 99%
“…Larger species possess SCG neurons which exhibit greater convergence, more complex arborizations and a greater proportion of axo-dendritic compared to axo-somatic synapses (Forehand, 1985;Purves and Lichtman, 1985;Purves et al, 1986). Therefore, in autonomic ganglia-including the SCG-a decision should be made to confine counts to axo-dendritic synapses rather than axo-somatic ones, since the former occur more frequently (Forehand, 1985;Gibbins and Morris, 2006;Loesch et al, 2010;Matthews, 1983).…”
Section: P0260mentioning
confidence: 99%
See 1 more Smart Citation